Does the Good Behavior Game evoke negative peer pressure? Analyses in primary and secondary classrooms. Issue 1 (26th September 2018) - Groves, Emily A.; Austin, Jennifer L.
Abstract : The Good Behavior Game (GBG) is a classroom management system that employs an interdependent group contingency, whereby students work as a team to win the game. Although previous anecdotal data have suggested that this arrangement may promote prosocial behavior, teachers may have concerns about its fairness and potential to evoke negative peer interactions (especially toward students who break the rules). We evaluated disruptive behaviors and social interactions during the GBG in a secondary classroom for students with emotional and behavioral disorders, as well as in a primary classroom for students with mild developmental disabilities. Results indicate that the GBG reduced disruptive behaviors; further, negative peer interactions decreased and positive interactions increased when the game was being played. Social validity results indicate that the majority of students thought the interdependent group contingency was fair.